2023
DOI: 10.2337/dc22-0385
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Incident Type 1 Diabetes to Recent COVID-19 Infection: Cohort Study Using e-Health Record Linkage in Scotland

Abstract: OBJECTIVE Studies using claims databases reported that SARS-CoV-2 infection >30 days earlier was associated with an increase in the incidence of type 1 diabetes. Using exact dates of diabetes diagnosis from the national register in Scotland linked to virology laboratory data, we sought to replicate this finding. RESEARCH DESIGN AND METHODS A cohort of 1,849,411 individuals aged <35 years without diabetes, includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 25 publications
6
62
4
2
Order By: Relevance
“…Risk estimates were lower when the comparison population was AURI (Hazard Ratio: 2.66 (1.98-3.56) vs. non-COVID-19 (2.16 (1.64-2.86). In Scotland, [30] no increased risk was observed in people with vs. without COVID-19 aged <35 years, and in another US study, non-hospitalized and hospitalized children aged <20 years with COVID-19 had a 27% and 114% increased risk of diabetes as compared to people without COVID-19, respectively. [34] Finally, in another US study, new-onset diabetes was increased in children aged 10-18 years at 3 months (HR: 2.40 (1.62-3.56)) and 6 months (HR: 2.18 (1.57-3.03), but not in children aged 0-9 years.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Risk estimates were lower when the comparison population was AURI (Hazard Ratio: 2.66 (1.98-3.56) vs. non-COVID-19 (2.16 (1.64-2.86). In Scotland, [30] no increased risk was observed in people with vs. without COVID-19 aged <35 years, and in another US study, non-hospitalized and hospitalized children aged <20 years with COVID-19 had a 27% and 114% increased risk of diabetes as compared to people without COVID-19, respectively. [34] Finally, in another US study, new-onset diabetes was increased in children aged 10-18 years at 3 months (HR: 2.40 (1.62-3.56)) and 6 months (HR: 2.18 (1.57-3.03), but not in children aged 0-9 years.…”
Section: Resultsmentioning
confidence: 88%
“…Overall, 12/14 (86%) studies reported that COVID-19 was associated with an 11% to 276% increased risk for incident diabetes, with risk estimates varying depending on comparison population (i.e., non-COVID-19 vs. acute upper respiratory infection (AURI)), hospitalization status, and age (i.e., adults vs. children). Of the two studies that report no association, one examined any new diabetes diagnosis in 1.85 million people aged <35 years (i.e., Type 1 diabetes) in Scotland (Hazard Ratio: 0.86, 95%CI: 0.62-1.21) [30] and the other examined new-onset diabetes 12-months after hospitalization with acute pancreatitis (and with vs. without COVID-19 infection) (OR: 0.61 (0.13-2.96). [31] …”
Section: Resultsmentioning
confidence: 99%
“…Besides, a study of two large databases of more than 2.5 million children indicated that those with COVID-19 presented a higher risk of new diabetes than those without COVID-19 [18]. An analysis, which is not yet peer-reviewed, of 1.8 million people aged younger than 35 years also suggested an increased risk of diabetes within, but not beyond, the first 30 days after SARS-CoV-2 infection [34].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we conducted a sensitivity analysis to confirm the robustness of our findings. Specifically, the irregular visiting times were firstly modeled, and the generalized estimating equation (GEE) is then fitted with inverse-intensity-of-visit-process weighting (22; 23). The effect sizes in propensity score strata were then aggregated using fixed-effect meta-analysis.…”
Section: Methodsmentioning
confidence: 99%